A generalized framework for seawater reverse osmosis design beyond energy minimization through brine and cost trade-offs: Design atlas for two-stage SWRO systems - Muhammad H. Elbassoussi; Omar G. Kaoud; Syed M. Zubair (Water Research, 2026)

Highly selective solar CO2 conversion into ethanol over metal-free sulfonated g-C3N4/nitrogen doped reduced graphene oxide hybrid photocatalyst - Sachin G. Ghugal; Amol U. Pawar; Park Kyoung Mo; Poonchi Sivasankaran Ramesh; Harish Reddy Inta; Sanjeev Gupta; Sung-hoon Oh; Muhammad Zaeem Azam Khan; Young Seok Son; Hyunchul Shin; Hongxian Han; Young Soo Kang (Chemical Engineering Journal, 2026)

Maternal and early-life arsenic exposure and relative telomere length in children: Findings from the BiRCH cohort - Lydia Lichtiger; Shohreh F. Farzan; Tariqul Islam; Syed Emdadul Haque; Mohammad H. Shahriar; Golam Sarwar; Alauddin Ahmed; Chunyu Liu; Brandon L. Pierce; Farzana Jasmine; Muhammad G. Kibriya; Habibul Ahsan; et al. (Environmental Research, 2026)

Techno-economic assessment of batch reverse osmosis desalination systems: Rating and design - Qais N. Al-Oweiti; Omar G. Kaoud; M.A.M. Ahmed; Faheem Ejaz; Muhammad H. Elbassoussi; Syed M. Zubair (Desalination, 2026)

Concerns regarding the article “Comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria” by Hamman et al. Toxicon 266 (2025) 108510 - Muhammad Hamza; Garba Ilyasu; Hamman A. Nicholas; Mohammed B. Saiyejo; Titus B. Dajel; Abubakar B. Saidu; Bashir Dansanda; Hayatuddeen Saed; Kabir S. Tahir; Bashir Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2026)

Artificial Intelligence-assisted Discovery of Novel Bilastine and Bepotastine Analogs Against the Histamine H1 Receptor: Integrated Molecular Dynamics and MM/PBSA Evaluation - Muhammad Husnain; Shabbir Muhammad; Shamsa Bibi; Shafiq ur Rehman; Abdullah G. Al-Sehemi; Shimmaa Mansour Moustafa Mohamed; Saleh S. Alarfaji (Journal of Pharmaceutical Innovation, 2026)

Assessing stand development controls on carbon sequestration and carbon credit value in tropical introduced teak plantation - John Oluwafemi Ayoola; Babatunde Oluseyi Ajiboye; Abraham Olanrewaju Opanike; Fahim Arshad; Shiekh Marifatul Haq; Adetayo Olubunmi Odunola; Aderinola Adeola Deborah; Muhammad Waheed; Ismoilov Ibrokhim; Muydinov Nurillo Tukhtarovich; Tursunqulov Jasur Baxtiyorovich; Mamatov Hurshidbek Mirzakamol o‘g‘li (Environmental Monitoring and Assessment, 2026)

Case Report: Detection of a Caprine Coccidian Parasite in a Neonatal Bengal Tiger Cub (Panthera tigris tigris) at Grand Taman Safari Prigen, Indonesia - April H. Wardhana; Nanang T. Laksono; Jansen Manangsang; Frenky L. Putra; Dyah H. Sawitri; Muhammad R. Maulana; Aldi G. R. Tanjung; Muhammad A. Kurnianto; Aditya Yudhana; Kartika Dewi; Makoto Matsubayashi (Acta Parasitologica, 2026)

Whither hydrology? Looking back to move ahead - Allen G. Hunt; Muhammad Sahimi; Behzad Ghanbarian (Hydrological Sciences Journal, 2026)

Left behind: forgone medical care due to transportation barriers among adults with physical impairments and disabilities that prevent physical activity in small and rural communities - Jiahe Bian; Wei Li; Xiao Li; Sun Quan; Andong Chen; Sinan Zhong; Muhammad Usman; Samuel Dominic Castiglione Towne; Muyang Li; Bahar Dadashova; Xinyue Ye; Marcia G. Ory (Travel Behaviour and Society, 2026)

Conservation and management implications of genetic and geometric scale variation in the ancient fish giant featherback ( Chitala lopis ) - Boby Muslimin; Gunawan Muhammad; Arif Wibowo; Kurniawan Kurniawan; Vitas Atmadi Prakoso; Rendy Ginanjar; Mochammad Zamroni; Bayu Kreshna Adhitya Sumarto; Septiana Sri Astuti; Deni Irawan; Agus Priyadi; Mirna Dwirastina; et al. (Journal of Fish Biology, 2026)
Giant featherback ( Chitala lopis ) is an ancient species of freshwater fish considered globally extinct until extant populations were re‐discovered in the Sundaland region of Indonesia in 2022. To improve management of the remaining populations, this study used genomic DNA and landmark‐based geometric morphometric analyses of fish scales to evaluate whether these approaches can discriminate among phylogenetic clades, sexes and broad habitat ecotypes inhabited by extant C. lopis populations. DNA analyses of 39 specimens from eight rivers provided the first evidence of two phylogenetic clades: (i) those from Central and South Borneo and (ii) those from West Borneo, Riau, South Sumatra and Jambi. Scale morphology was characterised across eight body areas using scale dimensions (relative height and width to standard length and height‐to‐width ratio), centroid size and Procrustes shape coordinates, with repeated‐measures structure accounted for using linear mixed models and Procrustes ANOVA with a randomised residual permutation procedure (RRPP). Scale dimensions and centroid size varied significantly among body areas (all p p = 0.024), with Clade 2 individuals consistently showing lower values than Clade 1, though scale geometry overall showed limited promise as a rapid non‐destructive stock discriminator. Both clade and sex had small but significant effects on Procrustes scale shape ( R 2 = 0.015 and 0.013, respectively; both p = 0.001), while phenotypic trajectory analysis revealed that males exhibited a significantly greater amplitude of scale shape change across body positions than females (trajectory magnitude: M = 0.289, F = 0.207; p = 0.034), despite both sexes following parallel shape trajectories along the body axis. These results provide a novel morphometric baseline for C. lopis and highlight the importance of body‐position‐specific and multivariate approaches when characterising scale morphology in endangered freshwater fishes.

Synergistic enhancement of photocatalytic hydrogen evolution via NiSX-NiO/S-g-C3N4 heterojunctions under visible light irradiation - Muhammad A. Abo El-Khair; Asmaa S. Morshedy; Abdalrahman G. Al-Gamal (Fuel, 2026)

Application of advanced oxidation processes for remediation of rubber industry wastewater: a comprehensive review - Zafran Ullah; Zhen-Yu Tian; Collin G. Joseph; Sabine Neusatz Guilhen; Siow Hwa Teo; Jualang Azlan Gansau; Rosalam Sarbatly; Kartini Alias; Pretibaa Subhramaniyun; Muhammad Naeem Khan; Muhammad Shahid Iqbal (Environmental Science and Pollution Research, 2026)

Metabolic fate of montmorency tart cherry (Prunus cerasus L.) polyphenols and their association with short-chain fatty acids in humans: A secondary analysis - Muhammad Jawad; Stephen T. Talcott; Robert G. Brannan; Angela R. Hillman (Food Bioscience, 2026)

A review of premise plumbing systems: from design and key performance domains to challenges and future research pathways for full-scale integration - Muhammad Bilal; Steven G. Sandi; Brendan M. Josey; Jinzhe Gong (Water Research, 2026)

Techno-economic optimization of large-scale two-stage brackish water reverse osmosis systems using dimensionless modeling - Muhammad H. Elbassoussi; Omar G. Kaoud; Syed M. Zubair (Water Research, 2026)

Renewable–diesel-powered multi-element series SWRO for off-grid Sinai resorts: A multi-objective optimization for cost‑carbon minimization - Omar G. Kaoud; Muhammad H. Elbassoussi; M.A. Abido; Syed M. Zubair (Desalination, 2026)

Direct air capture with solid sorbents: Adsorbent design, process engineering, and CO2 conversion - Muhammad Hassan; Changdon Shin; Taekgi Lee; Seunghyun Lee; Somnath Chowdhury; Hyuk Taek Kwon; Sung Gu Kang; Sol Ahn; Yongchul G. Chung (Chemical Engineering Journal, 2026)

Green-engineered CSPVA@CuO–Ag hybrid nanocomposite for methylene blue removal: a comprehensive adsorption study - S. K. Lakkaboyana; A. Muhammad; E. A. Abdelrahman; K. Neeli; P. Venkateswarlu; R. M. N. Kalla; A. G. Alhamzani (International Journal of Environmental Science and Technology, 2026)

Gypsum and Manure Impacts on Contrasting Textured Saline-Sodic Soils and Greenhouse Gas Emissions - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Muhammad Sabir; Aftab Jamal; Ayesha Abdul Qadir; Bryan G. Hopkins; Muhammad Nadeem Ashraf (Journal of Soil Science and Plant Nutrition, 2026)

In Vitro Permeation Testing of Sunscreens using Reconstructed Human Skin versus Human Cadaver Skin Models - Kartik R. Roy; Apipa Wanasathop; Lijing Xu; Jiang Wang; Sergio G. Coelho; Steven A. Adah; Theresa M. Michele; Patrick J. Faustino; Muhammad Ashraf; Xiaoming Xu; Yang Yang (AAPS PharmSciTech, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Cytotoxic secondary metabolites from submerged cultures of Chaetomium sp. isolated from decaying wood - Bel Youssouf G. Mountessou; Gesquiere Laure M. Tiani; Joseph Tchamgoue; Rukesh Maharjan; Aron Trucksess; Rainer Kalscheuer; Muhammad I. Choudhary; Simeon F. Kouam (Phytochemistry Letters, 2026)

Understanding green house gases emission dynamics from forest fires in Thailand using predictive models - Fahad Shahzad; Kaleem Mehmood; Shoaib Ahmad Anees; Muhammad Adnan; Khadim Hussain; Waseem Razzaq Khan; Munawar Shah; Punyawi Jamjareegulgarn; Manuela Oliveira; José G. Borges (Global and Planetary Change, 2026)

AIM: A user-friendly GUI workflow program for isotherm fitting, mixture prediction, isosteric heat of adsorption estimation, and breakthrough simulation - Muhammad Hassan; Sunghyun Yoon; Yu Chen; Pilseok Kim; Hongryeol Yun; Hyuk Taek Kwon; Youn-Sang Bae; Chung-Yul Yoo; Dong-Yeun Koh; Chang Seop Hong; Ki Bong Lee; Yongchul G. Chung (Computer Physics Communications, 2026)

Linalool exerts antiemetic effects via dopaminergic and serotonergic pathways: Evidence from chick model and molecular docking - Abdullah Al Fahmi; Khadija Akter; Imam Hossen Rakib; Sakib Hossain; Ali G. Alkhathami; Md. Sakib Al Hasan; Rakib Hossan; Iffat Ara; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Linalool (LIN), a naturally occurring monoterpene alcohol found in aromatic plants, exhibits diverse pharmacological properties, yet its antiemetic potential remains underexplored. In this study, we investigated the antiemetic efficacy of LIN using both in vivo and in silico approaches. Emesis was induced in chicks via oral administration of copper sulfate pentahydrate (50 mg/kg), and LIN was tested at doses of 25, 50, and 100 mg/kg. Its effects were compared against the standard antiemetics domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg). Results demonstrated that LIN at 100 mg/kg significantly prolonged the emetic latency and reduced the number of retches. Notably, co-administration of LIN (50 mg/kg) with DOM significantly ( p < 0.05) produced the most potent effect, yielding the highest latency and lowest number of retches, reflecting a synergistic interaction. Molecular docking studies revealed a strong binding affinity of LIN to the dopamine D2 receptor (− 6.4 kcal/mol) and moderate binding to the 5-HT3 receptor (− 5.3 kcal/mol), suggesting involvement of both dopaminergic and serotonergic mechanisms. These findings collectively indicate that LIN possesses significant antiemetic activity and may offer a plant-derived alternative for emesis control.

On dimensionless modeling of two-stage reverse osmosis: Thermodynamic and economic insights - Muhammad H. Elbassoussi; Omar G. Kaoud; Syed M. Zubair (Desalination, 2026)

Coalescent 2D heterostructure for high-efficient surface-enhanced Raman scattering and electrochemical sensing - Muhammad H. Nawaz; S. Santhoshkumar; Thi H. Ho; Balamurugan Arumugam; Mohamed Gamal Mohamed; Tuan V. Vu; Yousra.M. Nabil; Mohammed G. Kotp; Li-Wei Tu; Hung-Duen Yang; Ahmed F.M. EL-Mahdy; Shiu-Ming Huang; et al. (Chemical Engineering Journal, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

Which antiplatelet is better after stents? A meta-analysis of aspirin vs clopidogrel in the maintenance phase - Omar Almaadawy; Mohamed Elnady; Hossam Elbenawi; Ahmed Almahdy Mohamed; Abdelrahman Elshimy; Menna Sarhan; Abdul Rhman Hassan; Eman Moheyeldin; Alshaimaa G. Mohamed; Nada Ali; Muhammad Eltony; Abdalla Elmansoury; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Laboratory and greenhouse endophytic colonization of tomato by three entomopathogenic fungal isolates for the management of Tetranychus urticae and field efficacy trials - Waqas Wakil; Maria C. Boukouvala; Nickolas G. Kavallieratos; Aqsa Naeem; Syed Adnan Haider; Muhammad Usman Ghazanfar; Pasco B. Avery (Crop Protection, 2025)

Subject: Concerns regarding the article “comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria” by Hamman et al. Toxicon 266 (2025) 108510 - Garba Iliyasu; Saidu B. Abubakar; Nicholas A. Hamman; Titus B. Dajel; Muhammad Hamza; Basheer Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2025)

Subject: Concerns regarding the article “comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria” by Hamman et al. Toxicon 266 (2025) 108510 - Muhammad Hamza; Titus B. Dajel; Nicholas A. Hamman; Saidu B. Abubakar; Garba Iliyasu; Basheer Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2025)

Corrigendum to “Spatial distribution of juvenile corals (Scleractinia) in the coastal and small islands of Sumatra, Indonesia” [Reg. Stud. Mar. Sci. 80 (2024) 103857] - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Giyanto; Risandi D. Putra; Ni Wayan P. Sari; Rikoh M. Siringoringo; Tri A. Hadi; Rizkie S. Utama; Bambang Hermanto; Ucu Y. Arbi; et al. (Regional Studies in Marine Science, 2025)

Corrigendum to “Spatio- temporal juvenile corals (Scleractinia) following the 2016 coral bleaching event at the Pieh Islands Marine Tourism Park (PIMTP), West Sumatra Province, Indonesia” [Reg. Stud. Mar. Sci. 75 (2024) 103533] - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Rikoh M. Siringoringo; Tri Aryono Hadi; Giyanto; Raden Sutiadi; Ana Faricha; Yuwanda Ilham; et al. (Regional Studies in Marine Science, 2025)

Comparative effects of nano and conventional molybdenum fertilizers on oilseed rape growth and yield under acidic soil conditions - Muhamad Syaifudin; Mohamed G. Moussa; Muhammad Shoaib Rana; Parashuram Bhantana; Yiwen Wang; Chengxiao Hu; Xuecheng Sun (Biocatalysis and Agricultural Biotechnology, 2025)

A non-linear statistical framework to investigate changes in life history patterns within and among fish populations - Clement Z. W. Ng; Patrick Reis-Santos; Júlio G. Gonzalez; Bronwyn M. Gillanders; Muhammad F. Saleh; Joyce J. L. Ong (Reviews in Fish Biology and Fisheries, 2025)
Understanding movement patterns is crucial for predicting species responses to environmental change. However, in aquatic environments, the lack of long-term movement data constrains our ability to interpret how species adapt to changing conditions. Fish otoliths provide insights into individual life-history strategies via time-resolved chemical signatures but disentangling interactions between physiological and environmental processes remain challenging. Current analytical approaches often categorise life-history profiles into qualitative groups, based on sampling regions or years, overlooking intra-annual variation and simplifying data to group-level means. This study introduces a non-linear statistical framework using Generalised Additive Mixed Models (GAMMs) to explore how otolith element concentrations (Mg:Ca, Sr:Ca, Ba:Ca) vary with demographic variables (Age, Region) and temporal effects in a tropical snapper and illustrates its application on Lutjanus malabaricus across the Indo-Pacific region. Our findings revealed significant, non-linear changes in otolith Sr:Ca, reflecting shared and region-specific age patterns, suggesting that despite geographic separation, phylogenetic processes affecting Sr regulation remained consistent between regions. In contrast, distinct region-specific age differences in Ba:Ca and Mg:Ca highlight the influence of environmental and/or physiological processes on otolith chemistry. Incorporating random effects refined our analysis by accounting for temporal dependencies and individual-specific age patterns. Overall, this non-linear framework provides a powerful approach to unravelling the complex life-history and movement strategies in fish populations, providing critical insights into their adaptive responses to changing environments. Beyond otoliths, this framework can be applied to analyse continuous, time-resolved chemical data from accretionary structures across aquatic taxa, capitalising on the diverse ecological information archived across the natural world.

Assessing long-term vegetation changes, pollution and climate response in the Uttarakhand Region, North India: implications of Google Earth Engine - Umesh Chandra Dumka; Kiran Rawat; Dimitris G. Kaskaoutis; Ankur Srivastava; Muhammad Bilal; Sanjeev Kimothi; Prasun Kumar Gupta; Nikul Kumari (Environmental Monitoring and Assessment, 2025)

Comparative clinical observations following introduction of a new polyvalent antivenom for snakebite envenoming in northern Nigeria - Nicholas A. Hamman; Titus B. Dajel; Mohammed B. Saiyejo; Saidu B. Abubakar; Bashir Dansanda; Hayatu Saeedu; Kabiru Tahir; Muhammad Hamza; Garba Iliyasu; Basheer Z. Chedi; Abdulrazaq G. Habib (Toxicon, 2025)

Tart cherry (Prunus cerasus L.): Polyphenols, bioactivity, and bioavailability beyond exercise - Muhammad Jawad; Angela R. Hillman; Robert G. Brannan (Food Bioscience, 2025)

High take of mobulid rays in East Java, Indonesia: landing trends and socio-economic context - Betty J. L. Laglbauer; Muhammad G. Salim; Fahmi; Selvia Oktaviyani; Irianies C. Gozali; Firmansyah Tawang; Hasan S. Rizal; Vidlia P. Rosady; Didik Rudianto; Isabel Ender; Jorge M. R. Fontes; Pedro Afonso; et al. (Environmental Biology of Fishes, 2025)

Assessing virgin and reclaimed carbon fibre electrodes in structural batteries - James D. Randall; Aqeel Muhammad; Emma G. Hogan; Timothy Harte; Žan Simon; Bhagya Dhamarsiri; Leif E. Asp; Luke C. Henderson (Chemical Engineering Journal, 2025)

A dimensionless approach to minimizing energy consumption in single-pass reverse osmosis desalination systems - Muhammad H. Elbassoussi; Omar G. Kaoud; Syed M. Zubair (Water Research, 2025)

Time series data analysis to predict the status of mastitis in dairy cows by applying machine learning models to automated milking systems data - Muhammad N. Dharejo; Lukas Minogue; Tina Kabelitz; Thomas Amon; Olivier Kashongwe; Marcus G. Doherr (Preventive Veterinary Medicine, 2025)

Therapeutic innovations: targeting ROS production in AML with natural and synthetic compounds - Mohammed Hashim Mohammed; Raed Fanoukh Aboqader Al-Aouadi; Subasini Uthirapathy; Gaurav Sanghvi; Rekha M M; Resan Shakir Abdulamer; G. V. Siva Prasad; Mayank Kundlas; Fayzulla Khamraev; Muhammad Ikram Ullah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Inferring shallow storage properties from the analysis of percolation theory of streamflow elasticity - Allen G. Hunt; Behzad Ghanbarian; Muhammad Sahimi (Science of The Total Environment, 2025)

Evaluation of the Water Quality Index of some Drains Linked to the Bahr El-Baqar Drain and Study of Heavy Metals in Vegetables Grown Around Them and Their Potential Risks to the Health - Haifa A. S. Alhaithloul; Khalid G. Soliman; Ahmed H. Ibrahim; Awatif M. Abdulmajeed; Alaa Muqbil Alsirhani; Mohamed A. Abdein; Mesfer M. Alqahtani; Fauzeya Mateq Albalwe; Muhammad Tahir; Maha M. Elshamy; Elmadawy G. A. Kedra; Gamal A. Zayed; et al. (Water, Air, & Soil Pollution, 2025)

A Bayesian framework for crop model calibration: A case study in the US Corn Belt - Matteo G. Ziliani; Muhammad U. Altaf; Trenton E. Franz; Bangyou Zheng; Scott Chapman; Justin Sheffield; Ibrahim Hoteit; Matthew F. McCabe (European Journal of Agronomy, 2025)

Advancements in the production methods and recycling of multilayer plastics with sustainable applications: A comprehensive review - Maha Awjan Alreshidi; Krishna Kumar Yadav; G. Shoba; Amel Gacem; S. Padmanabhan; T. Vinod Kumar; Ahmed M. Fallatah; Javed Khan Bhutto; Fahad M. Aldosari; Manawwer Alam; Muhammad A. Abo El-Khair; P. Tamizhdurai; et al. (Chemical Engineering Journal, 2025)

A step towards rational design of hierarchical porous MOFs architectures for emerging practical implementations - Muhammad Umar Farooq; Rustem R. Zairov; Marsil K. Kadirov; Oleg G. Sinyashin; Bassim Arkook; Moussab Harb (Chemical Engineering Journal, 2025)

Turn-On-Fluorescence Sensor and Solid Sensory Chip for Cyanide Detection - Muhammad Zahid; Nadeem Raza; Samuel Bonne; Mostafa E. Salem; Negin G. Niksirat; Muhammad Zeshan; Muhammad Rafiq; Jian Zhang; Muhammad Saleem (Journal of Fluorescence, 2025)

Electrocatalysis by design: Enhanced bifunctional activity of exfoliated graphite rod modified with NiCo porous layers towards overall water splitting - Abdelraouf A. Abdelraouf; Ahmed M. Abdelrahim; Muhammad G. Abd El-Moghny; Mohamed S. El-Deab (Journal of Environmental Chemical Engineering, 2025)

On the electrostatic solitary waves in an electron–positron–ion plasma with Cairns–Tsallis distributed electrons - Albandari W. Alrowaily; Muhammad Khalid; Abdul Kabir; C. G. L. Tiofack; Weaam Alhejaili; Sherif M. E. Ismaeel; Samir A. El-Tantawy (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Contrasting environmental and demographic influences on growth variability in two tropical snappers spanning the equator in the Indo-West Pacific - Clement Z. W. Ng; Julio G. Gonzalez; Muhammad F. Saleh; Corey B. Wakefield; Stephen J. Newman; Joyce J. L. Ong (Reviews in Fish Biology and Fisheries, 2025)

Harmonizing soil carbon simulation models, emission factors and direct measurements used in LCA of agricultural systems - Simone Pelaracci; Pietro Goglio; Simon Moakes; Marie Trydeman Knudsen; Klara Van Mierlo; Nina Adams; Fossey Maxime; Alberto Maresca; Manuel Romero-Huelva; Muhammad Ahmed Waqas; Laurence G. Smith; Frank Willem Oudshoorn; et al. (Agricultural Systems, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Synergistic TaW-based catalysts on date seed-derived activated carbon for sustainable cleaner energy fuel production via electrochemical valorization of furfural - Muhammad Ashraf Sabri; Israa Othman; G. Bharath; Hanifa Taher Alblooshi; Mohammad Abu Haija; Ricardo P. Nogueira; Fawzi Banat (Fuel, 2025)

Techno-economic evaluation of solar photovoltaic-powered reverse osmosis desalination for different locations in Saudi Arabia - Muhammad H. Elbassoussi; Omar G. Kaoud; Syed M. Zubair (Desalination, 2025)

The interplay of p16INK4a and non-coding RNAs: bridging cellular senescence, aging, and cancer - Ashok Kumar Balaraman; Muhammad Afzal; Ehssan Moglad; M. Arockia Babu; G. Padma Priya; Pooja Bansal; Sumit Rajotiya; Benod Kumar Kondapavuluri; Imran Kazmi; Sami I. Alzarea; Kavita Goyal; Haider Ali (Biogerontology, 2025)

Integrating industry 4.0 for enhanced sustainability: Pathways and prospects - M. Imran Khan; Tabassam Yasmeen; Mushtaq Khan; Noor Ul Hadi; Muhammad Asif; Muhammad Farooq; Sami G. Al-Ghamdi (Sustainable Production and Consumption, 2025)

Innovative circular bioeconomy and decarbonization approaches in palm oil waste management: A review - Kai Chen Goh; Tonni Agustiono Kurniawan; G. Abdulkareem AlSultan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Choo Wou Onn; Ta Wee Seow; et al. (Process Safety and Environmental Protection, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

Advancing electrochemical water desalination: Machine learning-driven prediction and RSM optimization of activated carbon electrodes - Abdul Hai; Muhamad Fazly Abdul Patah; Muhammad Ashraf Sabri; G. Bharath; Fawzi Banat; Wan Mohd Ashri Wan Daud (Desalination, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Exogenous application of melatonin and jasmonic acid protects the sugar beet from heat stress by modulating the enzymatic antioxidants deference mechanism and accumulation of organic osmolytes - Muhammad Irfan; Ahmed Abou El-Yazied; Muhammad Sheeraz; Shabir Hussain; Abdul Sattar; Qasim Ali; Hany G. Abd El-Gawad; Fahad Mohammed Alzuaibr; Maha Mohammed Alharbi; Siham M. Al-Balawi; Doaa Bahaa Eldin Darwish; Eldessoky S. Dessoky; et al. (Acta Physiologiae Plantarum, 2025)

Pathways and risk analysis of arsenic and heavy metal pollution in riverine water: Application of multivariate statistics and USEPA-recommended risk assessment models - Kifayatullah Khan; Muhammad Sajawal Khan; Muhammad Younas; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Chao Su; Niaz Ali; Afsheen Maryam; Ruoyu Liang (Journal of Contaminant Hydrology, 2025)

Synthesis and doping of alkali metals on MOF-74 for CO2 and CH4 pure and binary mixtures adsorption - Sami Ullah; Mohamad Azmi Bustam; Muhammad Sagir; Muhammad Rafi Raza; Saleem Nawaz; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Ahmad Mukhtar; Chong Li Feng; Muhammad Ayoub (Gas Science and Engineering, 2025)

Optimization of Extreme Learning Machine with Metaheuristic Algorithms for Modelling Water Quality Parameters of Tamburawa Water Treatment Plant in Nigeria - Sani I. Abba; Quoc Bao Pham; Anurag Malik; Romulus Costache; Muhammad Sani Gaya; Jazuli Abdullahi; Sagiru Mati; A. G. Usman; Gaurav Saini (Water Resources Management, 2025)

Dual-strategy approach for Rhynchophorus ferrugineus control: Endophytic Beauveria bassiana and Bacillus thuringiensis topical application - Muhammad Yasin; Waqas Wakil; Nickolas G. Kavallieratos; Nikoleta Eleftheriadou; Aqsa Naeem; Mirza Abdul Qayyum; Muhammad Asrar; Saleh S. Alhewairini; David Shapiro-Ilan (Crop Protection, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Impact of dairy wastewater on paddy rice cultivation, leachate microbes, and soil health under alternate wetting and drying irrigation - Juli Akter; Md. Touhidul Islam; Nusrat Jahan; Mohammed Mizanur Rahman; M. G. Mostofa Amin; Muhammad Tofazzal Hossain; A. K. M. Adham (Paddy and Water Environment, 2025)

Spatial distribution of juvenile corals (Scleractinia) in the coastal and small islands of Sumatra, Indonesia - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Giyanto; Risandi D. Putra; Ni Wayan. P. Sari; Rikoh M. Siringoringo; Tri A. Hadi; Rizkie S. Utama; Bambang Hermanto; Ucu Y. Arbi; et al. (Regional Studies in Marine Science, 2024)

Grain-Based Modeling for Heterogeneous Rock Fragmentation Under Stressed Conditions and TBM Cutter Spacing Optimization - Zheng Yang; Ming Tao; Tubing Yin; Muhammad Burhan Memon; P. G. Ranjith (Rock Mechanics and Rock Engineering, 2024)

Effects of dietary powdered Ficus deltoidea on the growth and health performance of African catfish, Clarias gariepinus production - Zulhisyam Abdul Kari; Suniza Anis Mohamad Sukri; Guillermo Téllez-Isaías; Walter G. Bottje; Martina Irwan Khoo; Ajay Guru; Jehad Zuhair Tayyeb; Muhammad Anamul Kabir; El-Sayed Hemdan Eissa; Albaris B. Tahiluddin; Lee Seong Wei (Fish Physiology and Biochemistry, 2024)

De novo assembly of sialotranscriptome of Hyalomma anatolicum and insights into expression dynamics in response to Theileria annulata infection - Adeel Mumtaz Abbasi; Shiza Nasir; Amna Arshad Bajwa; Haroon Akbar; Sara Artigas-Jerónimo; Clara Muñoz-Hernández; Marta Sánchez-Sánchez; Alberto Moraga-Fernández; Isabel G. Fernández de Mera; José de la Fuente; Muhammad Imran Rashid (Experimental and Applied Acarology, 2024)

Maternal arsenic exposure modifies associations between arsenic, folate and arsenic metabolism gene variants, and spina bifida risk: A case‒control study in Bangladesh - Chih-Fu Wei; Gwen Tindula; Sudipta Kumer Mukherjee; Xingyan Wang; Sheikh Muhammad Ekramullah; D.M. Arman; Md Joynul Islam; Mubinul Azim; Asifur Rahman; Shamantha Afreen; Md Ziaddin; Benjamin C. Warf; et al. (Environmental Research, 2024)

Spatio- temporal juvenile corals (Scleractinia) following the 2016 coral bleaching event at the Pieh Islands Marine Tourism Park (PIMTP), West Sumatra Province, Indonesia - Muhammad Abrar; Dietriech G. Bengen; Neviaty P. Zamani; Suharsono; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Rikoh M. Siringoringo; Tri Aryono Hadi; Giyanto; Raden Sutiadi; Ana Faricha; Yuwanda Ilham; et al. (Regional Studies in Marine Science, 2024)

Improving green hydrogen production: Microwave-assisted synthesis of diverse Ni-based nanocatalysts on Al2O3 for thermochemical water splitting - Salma Samidin; Wan Nor Roslam Wan Isahak; Khairul Naim Ahmad; N. Asikin Mijan; Muhammad Rahimi Yusop; Alinda Samsuri; G. Abdulkareem-Alsultan; Mohd Ambar Yarmo (Fuel, 2024)

A review of heavy metals pollution in riverine sediment from various Asian and European countries: Distribution, sources, and environmental risk - Maria Zeb; Kifayatullah Khan; Muhammad Younas; Abida Farooqi; Xianghui Cao; Yasar N. Kavil; Saeed Saad Alelyani; Mohammed M. Alkasbi; Abdullah G. Al-Sehemi (Marine Pollution Bulletin, 2024)

How water stability relates with timing, size, and community successions of harmful algal blooms: A case study in the Three Gorges Reservoir - Xuexing Yao; Zenghui Song; Guanglang Yang; Muhammad Waqas Yonas; Paul B. Hamilton; Amechi S. Nwankwegu; Oluwafemi Adeyeye; Wei Huang; Xiaojiao Luo; Abdelrahman M. Hassaan; G. Douglas Haffner; Lei Zhang (Marine Pollution Bulletin, 2024)

Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Zeshan Ali Sandhu; Umme Farwa; Muhammad Danish; Muhammad Asam Raza; Aqib Talib; Hifza Amjad; Rukhmah Riaz; Abdullah G. Al-Sehemi (Journal of Cleaner Production, 2024)

Consumer pesticide concerns and the choice of fruit and vegetable markets in five low- and middle-income countries - Justice A. Tambo; Monica K. Kansiime; Jayanthi R. Alaganthiran; Muhammad Danish; Solomon A. Duah; Shah Faisal; Makaiko G. Khonje; Fredrick Mbugua; Ganeshamoorthy Rajendran (Global Food Security, 2024)

Multi-scale computational screening of all-silica zeolites for adsorptive separation of ternary (H2S/CO2/CH4) mixtures - Sunghyun Yoon; Muhammad Hassan; Yongchul G. Chung (Chemical Engineering Journal, 2024)

Molecular detection of Coxiella burnetii in ticks infesting wild and domestic animals in the Eastern region of Punjab, Pakistan - Freeha Amin; Shahzad Ali; Muhammad Imran; Nora G. Cleary; Michael E. von Fricken; Iahtasham Khan (Tropical Animal Health and Production, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Harmonizing methods to account for soil nitrous oxide emissions in Life Cycle Assessment of agricultural systems - Pietro Goglio; Simon Moakes; Marie Trydeman Knudsen; Klara Van Mierlo; Nina Adams; Fossey Maxime; Alberto Maresca; Manuel Romero-Huelva; Muhammad Ahmed Waqas; Laurence G. Smith; Giampiero Grossi; Ward Smith; et al. (Agricultural Systems, 2024)

Silicon and Biochar Synergistically Stimulate Nutrients Uptake, Photosynthetic Pigments, Gaseous Exchange and Oxidative Defense to Improve Maize Growth Under Salinity - Sajid Mahmood; Samir G. Al-Solaimani; Samrah Shams; Sahar Naveed; Basit Haider; Muhammad Naveed; Rehmat Ali; Muhammad Waqas (Water, Air, & Soil Pollution, 2024)

Characterizing stalagmite composition using hyperspectral imaging - Ali Raza; Ny Riavo G. Voarintsoa; Shuhab D. Khan; Muhammad Qasim (Sedimentary Geology, 2024)

Boosted Bio-Jet production: Unveiling the potential of a one-stage concurrent process of deoxygenation/upgrading versus two-stage sequential processes using Pt/Cl-Al2O3@Ni/ZSM-5 catalysts - Muhammad A. Abo El-Khair; Samia A. Hanafi; Muhammad G. Abd El-Moghny; Mohamed El Saied; Mamdouh S. Elmelawy; Mohamed S. El-Deab (Chemical Engineering Journal, 2024)

Climate changes altered the citrus fruit quality: A 9-year case study in China - ZhiHao Dong; MengXin Chen; Anoop Kumar Srivastava; Ul Hassan Mahmood; Muhammad Ishfaq; XiaoJun Shi; YueQiang Zhang; Mohamed G. Moussa; XueXian Li; ChengXiao Hu; FuSuo Zhang (Science of The Total Environment, 2024)

Economic growth, nuclear energy, renewable energy, and environmental quality: Investigating the environmental Kuznets curve and load capacity curve hypothesis - Shuang Wang; Muhammad Wasif Zafar; Dinara G. Vasbieva; Suleyman Yurtkuran (Gondwana Research, 2024)

Sunlight-Driven Photocatalytic Degradation of Methylene Violet (MV) by Employing Samarium-Doped Tungsten Disulfide - Saba Zahra; Meznah M. Alanazi; Shaimaa A. M. Abdelmohsen; Saeed D. Alahmari; Fatimah A. M. Al-Zahrani; Abdullah G. Al-Sehemi; A. M. A. Henaish; Zubair Ahmad; Hafiz Muhammad Tahir Farid (Water, Air, & Soil Pollution, 2024)

Air quality and cancer risk in the All of Us Research Program - Andrew Craver; Jiajun Luo; Muhammad G. Kibriya; Nina Randorf; Kendall Bahl; Elizabeth Connellan; Johnny Powell; Paul Zakin; Rena R. Jones; Maria Argos; Joyce Ho; Karen Kim; et al. (Cancer Causes & Control, 2024)
Introduction The NIH All of Us Research Program has enrolled over 544,000 participants across the US with unprecedented racial/ethnic diversity, offering opportunities to investigate myriad exposures and diseases. This paper aims to investigate the association between PM 2.5 exposure and cancer risks. Materials and methods This work was performed on data from 409,876 All of Us Research Program participants using the All of Us Researcher Workbench. Cancer case ascertainment was performed using data from electronic health records and the self-reported Personal Medical History questionnaire. PM 2.5 exposure was retrieved from NASA’s Earth Observing System Data and Information Center and assigned using participants’ 3-digit zip code prefixes. Multivariate logistic regression was used to estimate the odds ratio (OR) and 95% confidence interval (CI). Generalized additive models (GAMs) were used to investigate non-linear relationships. Results A total of 33,387 participants and 46,176 prevalent cancer cases were ascertained from participant EHR data, while 20,297 cases were ascertained from self-reported survey data from 18,133 participants; 9,502 cancer cases were captured in both the EHR and survey data. Average PM 2.5 level from 2007 to 2016 was 8.90 μg/m 3 (min 2.56, max 15.05). In analysis of cancer cases from EHR, an increased odds for breast cancer (OR 1.17, 95% CI 1.09–1.25), endometrial cancer (OR 1.33, 95% CI 1.09–1.62) and ovarian cancer (OR 1.20, 95% CI 1.01–1.42) in the 4th quartile of exposure compared to the 1st. In GAM, higher PM 2.5 concentration was associated with increased odds for blood cancer, bone cancer, brain cancer, breast cancer, colon and rectum cancer, endocrine system cancer, lung cancer, pancreatic cancer, prostate cancer, and thyroid cancer. Conclusions We found evidence of an association of PM 2.5 with breast, ovarian, and endometrial cancers. There is little to no prior evidence in the literature on the impact of PM 2.5 on risk of these cancers, warranting further investigation.

Utilizing a Low-Cost Air Quality Sensor: Assessing Air Pollutant Concentrations and Risks Using Low-Cost Sensors in Selangor, Malaysia - Zaki Khaslan; Mohd Shahrul Mohd Nadzir; Hamimatunnisa Johar; Zhang Siqi; Nor Azura Sulong; Faizal Mohamed; Shubhankar Majumdar; Fatin Nur Afiqah Suris; Nor Syamimi Sufiera Limi Hawari; Jintu Borah; Maggie Ooi Chel Gee; Muhammad Ikram A. Wahab; et al. (Water, Air, & Soil Pollution, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Identification and molecular mapping of a major gene conferring resistance to Phytophthora sansomeana in soybean ‘Colfax’ - Feng Lin; Muhammad Salman; Zhanguo Zhang; Austin G. McCoy; Wenlong Li; Raju Thada Magar; Drew Mitchell; Meixia Zhao; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2024)

Polydatin as a potential candidate that alleviates lead poisoning: insights from biochemical and oxidative damage in lead-induced Wistar rats - Salisu M. Highab; Jamilu Ya’u; Muhammad G. Magaji; Dalhatu M. Shehu (Advances in Traditional Medicine, 2024)

Integrated application of biochar and chemical fertilizers improves wheat (Triticum aestivum) productivity by enhancing soil microbial activities - Muhammad Abdullah Aziz; Khalid Saifullah Khan; Rabia Khalid; Muhammad Shabaan; Abdulaziz G. Alghamdi; Zafer Alasmary; Mosaed A. Majrashi (Plant and Soil, 2024)

Clean approach for catalytic biodiesel production from waste frying oil utilizing K2CO3/Orange peel derived hydrochar via RSM Optimization. - Omar A. Mawlid; Hosam H. Abdelhady; Muhammad G. Abd El-Moghny; Aya Hamada; Fatma Abdelnaby; Mariam Kased; Shaimaa Al-Bajouri; Rashida A. Elbohy; Mohamed S. El-Deab (Journal of Cleaner Production, 2024)

Hydrothermal synthesis of ZnO@MoTe2 nanocomposite as excellent electrocatalyst for hydrogen evolution reaction (HER) - Saeed D. Alahmari; Salma Aman; Soumaya Gouadria; Sajjad Ahmad Khan; Abdullah G. Al-Sehemi; A.M.A. Henaish; Naseeb Ahmad; Zubair Ahmad; Taha Abdel Mohaymen Taha; Hafiz Muhammad Tahir Farid (Fuel, 2024)

Sustainable humidity control in the built environment: Recent research and technological advancements in thermal driven dehumidification systems - Muhammad Usman Saeed Akhtar; Sulaiman O. Fadlallah; Muhammad Imran Khan; Faisal Asfand; Sami G. Al-Ghamdi; Rakesh Mishra (Energy and Buildings, 2024)

A winning formula: sustainable control of three stored-product insects through paired combinations of entomopathogenic fungus, diatomaceous earth, and lambda-cyhalothrin - Waqas Wakil; Nickolas G. Kavallieratos; Nikoleta Eleftheriadou; Syed Adnan Haider; Mirza Abdul Qayyum; Muhammad Tahir; Khawaja G. Rasool; Mureed Husain; Abdulrahman S. Aldawood (Environmental Science and Pollution Research, 2024)
This research aimed to assess the effectiveness of Metarhizium robertsii , diatomaceous earth (Protect-It), and lambda-cyhalothrin, for the long-term protection of stored wheat against three destructive grain insect pests, Rhyzopertha dominica , Tribolium castaneum , and Trogoderma granarium . Different treatments were applied, both alone and in paired combinations in laboratory and persistence trials. Single treatments exhibited significantly lower mortality rates in comparison to the paired treatments for all tested insect species. Among the single treatments, lambda-cyhalothrin (Lamb) resulted in significantly higher mortality rates in laboratory trials, followed by diatomaceous earth (DE) and M. robertsii (Mr), with insignificant differences between Mr and DE. Evidently, DE exhibited the highest persistence after 120 days of storage for all insect species and initial exposures, although variations in mortality rates among treatments were mostly insignificant. Overall, the most effective treatment in terms of mortality in laboratory, and persistence trials, and progeny production was DE + Lamb, followed by Mr + Lamb, and Mr + DE for all tested insect species. In general, the most susceptible insect species was R. dominica , followed by T. castaneum and T. granarium . This research highlights the effectiveness of M. robertsii , DE, and lambda-cyhalothrin in providing prolonged protection of stored wheat against all the examined grain insect species.

Depositional and diagenetic controls on the reservoir quality of Early Miocene syn-rift deep-marine sandstones, NW Saudi Arabia - Muhammad Naveed Butt; Stephen G. Franks; Arif Hussain; Abduljamiu Olalekan Amao; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Journal of Asian Earth Sciences, 2024)

Duration-sensitive association between air pollution exposure and changes in cardiometabolic biomarkers: Evidence from a predominantly African American cohort - Jiajun Luo; Muhammad G. Kibriya; Farzana Jasmine; Afzal Shaikh; Zhihao Jin; Robert Sargis; Karen Kim; Christopher O. Olopade; Jayant Pinto; Habibul Ahsan; Briseis Aschebrook-Kilfoy (Environmental Research, 2024)

Nanoscale enhancements in perovskite-based photovoltaics - Sikandar Aftab; Xin Li; Sajjad Hussain; Muhammad Aslam; Altaf Hussain Rajpar; Abdullah G. Al-Sehemi (Chemical Engineering Journal, 2024)

Harnessing water fleas for water reclamation: A nature-based tertiary wastewater treatment technology - Muhammad Abdullahi; Iestyn Stead; Sophie Bennett; Rafael Orozco; Mohamed Abou-Elwafa Abdallah; Sara Jabbari; Lynne E. Macaskie; Alexandra Tzella; Stefan Krause; Bushra Al-Duri; Robert G. Lee; Ben Herbert; et al. (Science of The Total Environment, 2023)

Highly efficient PdNiB decorated over carbon supports for the electrochemical valorization of furfural and 5-hydroxymethylfurfural into fuels - Muhammad Ashraf Sabri; G. Bharath; Abdul Hai; Mohammad Abu Haija; Ricardo P. Nogueira; Fawzi Banat (Fuel, 2023)

Synthesis and characterization of nanobiochar from rice husk biochar for the removal of safranin and malachite green from water - Sadia Aziz; Bushra Uzair; Muhammad Ishtiaq Ali; Sundas Anbreen; Fatiha Umber; Muneeba Khalid; Alaa AA. Aljabali; Yachana Mishra; Vijay Mishra; Ángel Serrano-Aroca; Gowhar A. Naikoo; Mohamed El-Tanani; et al. (Environmental Research, 2023)

Waste heat recovery in iron and steel industry using organic Rankine cycles - Mohammad Ja'fari; Muhammad Imran Khan; Sami G. Al-Ghamdi; Artur J. Jaworski; Faisal Asfand (Chemical Engineering Journal, 2023)

Heavy metals in five commonly consumed fish species from River Swat, Pakistan, and their implications for human health using multiple risk assessment approaches - Kifayatullah Khan; Maria Zeb; Muhammad Younas; Hafiz Muhammad Adeel Sharif; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Noor Samad Shah; Xianghui Cao; Afsheen Maryam; Muhammad Qasim (Marine Pollution Bulletin, 2023)

Case fatality rate and burden of snakebite envenoming in children – A systematic review and meta-analysis - Garba Iliyasu; Farouq M. Dayyab; Godpower C. Michael; Muhammad Hamza; Maryam A. Habib; José M. Gutiérrez; Abdulrazaq G. Habib (Toxicon, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Marble trace element and C-O isotope geochemistry of the Paleoproterozoic Jingshan Group, North China: Insights into BIF formation during the Lomagundi-Jatuli Event - Yuanlin Chen; Huan Li; Shangyi Gu; Gary G. Lash; Chaoyang Zheng; Shige Chen; Dadou Li; Safiyanu Muhammad Elatikpo; Liuan Duan (Precambrian Research, 2023)

Compliance in small-scale fisheries is linked to fisher-trader relations: not fishers alone (Southeast Asian case study) - Laura G. Elsler; Muhammad Neil; Sebastian Ferse; Gabriela Navarrete Forero; Marion Glaser; Maja Schlüter (Reviews in Fish Biology and Fisheries, 2023)
Fisher-trader relations are influential in many small-scale fisheries worldwide. The ability to influence emergent fishing practices has shifted traders into focus of fisheries policy-making. Formal policies could be more effective if they were complementary to and build on an understanding of the role of traders, their interaction with fishers, and how these contribute to the emergence of compliant or non-compliant fishing practices. Here, we first compared fishing practices with policies to assess the latter's effectiveness in Indonesia, Spermonde. Second, we identified the roles and interactions of fisher-trader relations in shaping emergent fishing practices using the social-ecological action situation framework. We found that 6 out of 7 fishing practices were at least partially non-compliant with formal policies. Second, fisher-trader relations mediated by social norms enabled more fishing practices to emerge than those focused solely on selling and buying fish. Third, traders' interactions with other fishery actors enabled non-compliant fishing practices. These findings comprehensively characterize fishers' and traders' roles and interactions in the emergence of fishing practices. Policy effectiveness could be enhanced by engaging in traders' interactions with other fishery actors.

A prospective observational phase IV study on effectiveness of animal derived polyclonal antibody antivenoms against West African carpet viper (Echis romani) induced coagulopathy and mortality - Titus B. Dajel; Saidu B. Abubakar; Nasiru M. Dan-Amarya; Nyam A. Azi; Salisu Mu'azu; Muhammad Hamza; Garba Iliyasu; Muhammad Y. Gwarzo; Abdulrazaq G. Habib (Toxicon, 2023)

Modelling compound flooding: a case study from Jakarta, Indonesia - William G. Bennett; Harshinie Karunarathna; Yunqing Xuan; Muhammad S. B. Kusuma; Mohammad Farid; Arno A. Kuntoro; Harkunti P. Rahayu; Benedictus Kombaitan; Deni Septiadi; Tri N. A. Kesuma; Richard Haigh; Dilanthi Amaratunga (Natural Hazards, 2023)
The paper investigates compound flooding from waves, sea surge and river flow in northern Jakarta, Indonesia, which is a global hotspot of flooding, by combining process-based coastal and river models. The coastal hydrodynamic modelling of Jakarta Bay in Indonesia shows that coastal storms can lead to a substantial increase in sea water level due to wind and wave setup in the nearshore areas, including Muara Angke river inlet. The compound flood hazard from a range of flood scenarios was simulated and analysed. The results reveal that low-lying areas around the river inlet are prone to flooding even during regular, low-intensity storm events, while rarer storms caused extensive floods. Floods were not caused by direct overwashing of sea defences but by overspill of the banks of the river inlet due to high sea water level caused by wind set up, wave setup, and sea surge obstructing the drainage of the river and elevating its water level during storms. We also found that the sea level rise combined with rapid land subsidence will inundate the existing coastal flood defences during storms in future. The majority of the city will be below mean sea level by 2100. The overflow of existing coastal defences will lead to extensive flooding in northern, western, and eastern Jakarta unless the defences are upgraded to keep up with future sea level rise.

Iron deficiency and its epigenetic effects on iron homeostasis - Bashar Farida; Kasimu G. Ibrahim; Bilyaminu Abubakar; Ibrahim Malami; Muhammad B. Bello; Murtala B. Abubakar; Abdullahi Y. Abbas; Mustapha U. Imam (Journal of Trace Elements in Medicine and Biology, 2023)

Comparison of snakebite in children and adults in Nigeria - Garba Iliyasu; Titus B. Dajel; Saidu B. Abubakar; Nyam Agwom Azi; Nasiru M. Danamarya; Olusegun A. Obateru; Abdulhakim M. Dayyab; Muhammad Hamza; Olatunde A. Alabi; Abdulrazaq G. Habib (Toxicon, 2023)

Interpreting water demands of forests and grasslands within a new Budyko formulation of evapotranspiration using percolation theory - Allen G. Hunt; Muhammad Sahimi; Boris A. Faybishenko; Markus Egli; Behzad Ghanbarian; Fang Yu (Science of The Total Environment, 2023)

Synthesis and Characterizations of Graphene/Copper Ferrite for Efficient Arsenic Removal - M. Abdullah; G. Murtaza; Muhammad Azhar Khan (Water, Air, & Soil Pollution, 2023)

Growth responses of mixotrophic giant clams on nearshore turbid coral reefs - Kimberley Mills; Eleanor H. John; Duncan D. Muir; Nadiezhda Santodomingo; Kenneth G. Johnson; Muhammad Ali Syed Hussein; Sindia Sosdian (Coral Reefs, 2023)
Increasing evidence suggests that nearshore turbid coral reefs may mitigate bleaching of reef building calcifiers and play a critical role in the future of marine biodiversity in coastal areas. However, biomineralization processes on turbid reefs are relatively understudied compared to clear water counterparts and most published work focuses on corals. Here, we investigate how the mixotrophic giant clam Tridacna squamosa , a bivalve with ecological, cultural and economic significance, grows across a mosaic of less turbid to turbid reefs in the Coral Triangle. We construct growth chronologies from live and dead collected shells by measuring daily growth increments with petrography and scanning electron microscopy (SEM) to gain insight into growth rate on daily, seasonal and annual scales. We find annual growth is not significantly different across a turbidity gradient when scaled to ontogeny, while seasonal growth highly varies. K d (490) (a measurement positively correlated with turbidity) and chlorophyll- a are likely important factors driving seasonal growth on a turbid reef near a river, compared to sea surface temperature (SST), cloud cover and rainfall on a less turbid reef. On a daily scale, we investigate increment microstructure and spectral characteristics of chronologies, finding a relationship between tidal range and daily increments. Overall, our results indicate that light-enhanced calcification is likely most important in the less turbid reef, compared to heterotrophic feeding in the turbid reef. The trophic plasticity of T. squamosa may allow for its sustained growth in marginal conditions, supporting evidence that these habitats serve as important conservation hotspots for diverse reef building taxa.

Removal of ceftriaxone sodium antibiotic from pharmaceutical wastewater using an activated carbon based TiO2 composite: Adsorption and photocatalytic degradation evaluation - Muneeb Abdullah; Javed Iqbal; Muhammad Saif Ur Rehman; Usman Khalid; Fahad Mateen; Salman Noshear Arshad; Abdullah G. Al-Sehemi; Hamed Algarni; Omar A. Al-Hartomy; Tahir Fazal (Chemosphere, 2023)

Performance of the 20 minutes Whole Blood Clotting Test in detection, monitoring and antivenom therapy of West African Carpet viper (Echis romani) envenoming in resource constrained settings in Nigeria - Muhammad Hamza; Titus B. Dajel; Saidu B. Abubakar; Auwalu S. Hamza; Hadiza L. Abdullahi; Garba Iliyasu; Abdulrazaq G. Habib (Toxicon, 2023)

Intelligent based decision-making strategy to predict fire intensity in subsurface engineering environments - Muhammad Kamran; Ridho Kresna Wattimena; Danial Jahed Armaghani; Panagiotis G. Asteris; Izhar Mithal Jiskani; Edy Tonnizam Mohamad (Process Safety and Environmental Protection, 2023)

Application of molecularly imprinted electrochemical sensor for trace analysis of Metribuzin herbicide in food samples - Mohamed Atef Abdel Fatah; Muhammad G. Abd El-Moghny; Mohamed S. El-Deab; Rasha Mohamed El Nashar (Food Chemistry, 2023)

Levels of Genetic Variants Among Symptomatic Blastocystis Subtypes and their Relationship to Mucosal Immune Surveillance in the Precancerous Colons of Experimentally Infected Rats - Eman M. Hussein; Muhammad A. A. Muhammad; Abdalla M. Hussein; Sherine M. Elzagawy; Wafaa M. Zaki; Ashraf G. Temsah; Mohamed S. Badr; Maha M. Alabbassy (Acta Parasitologica, 2023)
Purpose The relationship between the genetic diversity of Blastocystis and immune surveillance in precancerous colons with blastocystosis is still under investigation. This study aimed to identify the genetic Blastocystis variants among 54 symptomatic human isolates and their relationship to mucosal immune surveillance in the precancerous polyps of experimentally infected rats. Methods Polymerase chain reaction and high-resolution melting (PCR/HRM) curves discriminated human symptomatic Blastocystis isolates into subtypes (STs)/intrasubtypes, which were orally administered to rats to induce experimental infection. Then, the mucosal immune responses of the infected colons were evaluated in relation to polyp formation through immunostaining to identify mucus MUC2 and determine mucosal immune cell (goblet, lymphocyte and mast) counts, secretory IgA levels and parasitic intestinal invasion. Results ST1, ST3, and ST4 were found in 18.5% (10/54), 54.7% (29/54), and 27.8% (15/54) of the samples, respectively. Then, the HRM curve discriminated ST3 into the wild, mutant, and heterozygous [17/54 (31.5%), 5/54 (9.3%), and 7/54 (12.9%)] intrasubtypes. ST1 and ST4 had no genetic variations. Precancerous polyps were detected in the colons of 40.5% of the infected rats. ST1 constituted 14.7% of these cases, while the wild, mutant, and heterozygous intrasubtypes of ST3 showed polyps in 12.9%, 5.5%, and 5.5% of cases, respectively. Only 1.9% of the polyps were related to ST4. MUC2 showed weak immunostaining in 44.5% of the infected colons, and 38.9% were polyp inducers. Low goblet cell numbers and high interepithelial lymphocyte counts were significantly associated with polyp formation, particularly with ST1 and wild ST3. Among the polyp inducers, high numbers of mast cells were detected in wild ST3 and ST4, while a low number was found with heterozygous ST3. The level of secretory IgA was low in polyp-inducing STs. Most of the results were statistically significant. Conclusion Immunosurveillance showed a potential relationship between ST1 and the ST3 intrasubtypes and precancerous polyps. This relationship may provide insight into the prevention and/or development of new immunotherapeutic strategies to combat colorectal cancer.

High potential of the genus Allanblackia (Guttiferae): Phytochemistry, pharmacology, and traditional uses over the past half-century - Bel Youssouf G. Mountessou; Joseph Tchamgoue; Iliassou L. Mouafon; Ivan R. Green; Muhammad I. Choudhary; Simeon F. Kouam (South African Journal of Botany, 2023)

High pressure CO2 adsorption onto Malaysian Mukah-Balingian coals: Adsorption isotherms, thermodynamic and kinetic investigations - Mustafa Abunowara; Mohamad Azmi Bustam; Suriati Sufian; Muhammad Babar; Usama Eldemerdash; Ahmad Mukhtar; Sami Ullah; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Su Shiung Lam (Environmental Research, 2023)

Highly charged solar evaporator toward sustainable energy transition for in-situ freshwater & power generation - Muhammad Sultan Irshad; Yabin Hao; Naila Arshad; Muneerah Alomar; Liangyou Lin; Xiuqiang Li; Swelm. Wageh; Omar A. Al-Hartomy; Abdullah G. Al-Sehemi; Van-Duong Dao; Hao Wang; Xianbao Wang; et al. (Chemical Engineering Journal, 2023)

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

A new ceramide and other constituents from the fruits of Ficus lutea Vahl (Moraceae) and their chemotaxonomic significance - Herman D. Sonfack Fozeng; Arno R. Nanfack Donfack; Marthe A. Tchuente Tchuenmogne; Billy Toussie Tchegnitegni; Marie G. Tsepeupon Matchide; Elodie Gaële Matheuda; Raymonde A. Dzatie Djoumbissie; Yves M. Mba Nguekeu; Silvère Augustin Ngouela; Muhammad Shaiq Ali; Maurice Ducret Awouafack; Mathieu Tene (Biochemical Systematics and Ecology, 2023)

Ameliorative role of dietary acidifier potassium formate on growth metrics, blood chemistry, gut health and well-being indices of rohu, Labeo rohita fingerlings - M. Junaid Sidiq; E. G. Jayaraj; Sanjay Singh Rathore; Raja Aadil Hussain Bhat; Muhammad Abdullah-Al Mamun; Ajay S Khandagale (Fish Physiology and Biochemistry, 2023)

Determining effect of tree on wheat growth and yield parameters at three tree-base distances in wheat/Jand (Prosopis cineraria) agroforestry systems - A. Khan; G. Ali Bajwa; X. Yang; M. Hayat; J. Muhammad; F. Ali; A. Quddoos; M. Amin; T. Ullah Khan; A. Ullah Khan (Agroforestry Systems, 2023)

Two are better than one: the combinations of Beauveria bassiana, diatomaceous earth, and indoxacarb as effective wheat protectants - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Abid Ali; Taha Yaseen; Muhammad Asrar (Environmental Science and Pollution Research, 2023)
The current study evaluates the efficacy of the entomopathogenic fungus Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae), diatomaceous earth (DE) (Protect-It), and the oxadiazine indoxacarb, at single or combined applications on wheat kernels, for the management of the rusty grain beetle, Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), and the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae). The study was conducted between November 2020 and August 2021 in Faisalabad under a complete randomized block design. The combination of DE + indoxacarb was the most efficient as it caused higher overall mortalities ranging between 59.34 and 100%, and lower overall progeny production ranging between 8.35 and 33.70 individuals per vial, than all other treatments. Beauveria bassiana alone exhibited the lowest mortality rates ranging between 22.33 and 47.76%, and the highest offspring emergence, ranging between 51.33 and 78.55 individuals per vial. Similar pattern was observed when persistence bioassays were conducted. For a period of 120 days, the DE + indoxacarb was the most powerful combination against all tested species, providing overall mortality rates between 17.06 and 63.80%. The overall progeny production was lower for the insect individuals exposed on wheat treated with the DE + indoxacarb combination, ranging between 13.66 and 52.23 individuals per vial, and higher for those exposed to B. bassiana alone, ranging between 44.03 and 107.67 individuals per vial, for the entire duration of storage. However, the efficacy of all treatments decreased gradually during the course of storage. The findings of the current study indicate that the combinations of entomopathogenic fungi, DE, and indoxacarb can be used for the prolonged protection of stored wheat from the tested noxious insect species of stored products. Further research, which will include other inert dusts in combination with entomopathogenic fungi and indoxacarb, may provide additional knowledge towards an effective management of noxious species occurring in storages.

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

GCS site selection in saline Miocene formations in South Louisiana - Muhammad Zulqarnain; Stephen O. Sears; Mehdi Zeidouni; Richard G Hughes; Douglas Carlson; Carlos F Rivera (International Journal of Greenhouse Gas Control, 2023)

Life cycle assessment of Indonesian canned crab ( Portunus pelagicus ) - Edi Iswanto Wiloso; Muhammad Romli; Bambang Arif Nugraha; Adisa Ramadhan Wiloso; Arief Ameir Rahman Setiawan; Patrik J. G. Henriksson (Journal of Industrial Ecology, 2022)
Indonesia is an archipelagic country with abundant marine wealth that makes it the world's second largest producer of fish after China. While most of Indonesia's capture marine fisheries (80%) are consumed domestically, around 90% of blue swimming crab (BSC) products are exported, mainly in cans. This makes up almost half of all BSC products on the global market, with the United States and the European Union being the main importers. We carried out a life cycle assessment (LCA) of canned BSC products from Indonesia. Our LCA evaluated the production of “one tonne of canned BSC” at market as a functional unit (FU), with a cradle‐to‐market system boundary, encompassing wild capture, preprocessing, processing, and distribution to the port of destination at home and abroad. The processing stage was found to be the highest contributor (hotspot) for most of the impact categories considered, mainly due to the use of tin cans for packaging. Despite producing less by‐catch, BSC caught with traps resulted in around threefold greater global warming impact per FU than those caught using nets. We also concluded that BSC meat produced in Java is environmentally preferable to that from Sumatra, as most of the shells were sold as coproducts. In addition to recycling and substitution of packaging materials, environmental improvements can also be obtained by increasing the number of shell‐processing facilities outside Java. The results of this study can be used by the Indonesian government to develop more sustainable practices to avoid overexploitation of BSC and limit its environmental impacts.

Combinations of Beauveria bassiana and spinetoram for the management of four important stored-product pests: laboratory and field trials - Waqas Wakil; Nickolas G. Kavallieratos; Erifili P. Nika; Mirza Abdul Qayyum; Taha Yaseen; Muhammad Usman Ghazanfar; Muhammad Yasin (Environmental Science and Pollution Research, 2022)
The current study examines the efficacy of the semi-synthetic insecticide spinetoram and entomopathogenic fungi Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae) as wheat protectants against the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), and the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), under laboratory and field trials. One dose of B. bassiana , i.e., 1 × 10 7 conidia/kg wheat, two doses of spinetoram, i.e., spine1: 0.05 ppm (mg/kg wheat), spine2: 0.1 ppm, and their combinations (Bb + spine1, Bb + spine2) were evaluated at 20, 25, and 30 °C. All treatments provided significantly higher mortality at 30 °C compared with the other two temperatures. Maximum mortality levels were observed in the treatments where B. bassiana was combined with the higher dose of spinetoram (0.1 ppm). All treatments reduced progeny production in comparison with the control groups. Maximum progeny reduction was observed at 30 °C, on wheat treated with the Bb + spine2 combination. The combination Bb + spine2 also provided elevated mortality rates in both laboratory and field persistence trials, but at 180 days caused moderate mortality to all tested insect species. Concerning progeny, at laboratory persistence trials, the combination Bb + spine2 exhibited the lowest offspring emergence to all tested species compared to the other treatments and control. Overall, our study showed that R. dominica was the most susceptible species followed by S. granarius , T. castaneum , and T. granarium . Our findings revealed that the combination of B. bassiana and spinetoram may be a useful tool for efficient and advanced integrated pest management strategies for long storage periods under multiple temperatures.

Modelling impacts of climate change on coastal West African rainfall - Christopher E. Ndehedehe; Muhammad Usman; Onuwa Okwuashi; Vagner G. Ferreira (Modeling Earth Systems and Environment, 2022)

Molybdenum Role in Nitrogen Bioavailability of Wheat-Soil System Using the Natural 15N Abundance Technique - Mohamed G. Moussa; Xuecheng Sun; Shaimaa El-Tohory; Abdelkader Mohamed; Muhammad Hamzah Saleem; Muhammad Riaz; Zhihao Dong; Lingzhi He; Chengxiao Hu; Marwa A. Ismael (Journal of Soil Science and Plant Nutrition, 2022)

Influence of biochar on trace element uptake, toxicity and detoxification in plants and associated health risks: A critical review - Natasha Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Muhammad Asif Naeem; Nabeel Khan Niazi; Filip M. G. Tack; James Anthony Ippolito; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2022)

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Isolation of the 3β-HSD promoter from Digitalis ferruginea subsp. ferruginea and its functional characterization in Arabidopsis thaliana - Noreen Aslam; Muhammad Sameeullah; Muhammet Yildirim; Mehmet Cengiz Baloglu; Buhara Yucesan; Andreas G. Lössl; Mohammad Tahir Waheed; Ekrem Gurel (Molecular Biology Reports, 2022)

In Vitro Testing of Sunscreens for Dermal Absorption: Method Comparison and Rank Order Correlation with In Vivo Absorption - Yang Yang; Ann-Marie Ako-Adounvo; Jiang Wang; Sergio G. Coelho; Steven A. Adah; Murali K. Matta; David Strauss; Theresa M. Michele; Jian Wang; Patrick J. Faustino; Thomas O’Connor; Muhammad Ashraf (AAPS PharmSciTech, 2022)

Molybdenum-Induced Effects on Grain Yield, Macro–micro-nutrient Uptake, and Allocation in Mo-Inefficient Winter Wheat - Mohamed G. Moussa; Xuecheng Sun; Marwa A. Ismael; Ali Mohamed Elyamine; Muhammad Shoaib Rana; Muhamad Syaifudin; Chengxiao Hu (Journal of Plant Growth Regulation, 2022)

In vitro dissolution testing models of ocular implants for posterior segment drug delivery - Muhammad Faris Adrianto; Febri Annuryanti; Clive G. Wilson; Ravi Sheshala; Raghu Raj Singh Thakur (Drug Delivery and Translational Research, 2022)
The delivery of drugs to the posterior segment of the eye remains a tremendously difficult task. Prolonged treatment in conventional intravitreal therapy requires injections that are administered frequently due to the rapid clearance of the drug molecules. As an alternative, intraocular implants can offer drug release for long-term therapy. However, one of the several challenges in developing intraocular implants is selecting an appropriate in vitro dissolution testing model. In order to determine the efficacy of ocular implants in drug release, multiple in vitro test models were emerging. While these in vitro models may be used to analyse drug release profiles, the findings may not predict in vivo retinal drug exposure as this is influenced by metabolic and physiological factors. This review considers various types of in vitro test methods used to test drug release of ocular implants. Importantly, it discusses the challenges and factors that must be considered in the development and testing of the implants in an in vitro setup. Graphical abstract

Laboratory and field studies on the combined application of Beauveria bassiana and fipronil against four major stored-product coleopteran insect pests - Waqas Wakil; Nickolas G. Kavallieratos; Muhammad Usman Ghazanfar; Muhammad Usman (Environmental Science and Pollution Research, 2022)

Sequence stratigraphy, depositional and diagenetic environments of the late Cambrian glauconite bearing oolitic limestones in the Kelan Section, Shanxi, China - Muhammad Riaz; G M Bhat; Khalid Latif; Tehseen Zafar; Shahid Ghazi (Journal of Earth System Science, 2022)

Using a smartphone on the move: do visual constraints explain why we slow walking speed? - Alejandro Rubio Barañano; Muhammad Faisal; Brendan T. Barrett; John G. Buckley (Experimental Brain Research, 2022)
Viewing one’s smartphone whilst walking commonly leads to a slowing of walking. Slowing walking speed may occur because of the visual constraints related to reading the hand-held phone whilst in motion. We determine how walking-induced phone motion affects the ability to read on-screen information. Phone-reading performance (PRP) was assessed whilst participants walked on a treadmill at various speeds (Slow, Customary, Fast). The fastest speed was repeated, wearing an elbow brace (Braced) or with the phone mounted stationary (Fixed). An audible cue (‘text-alert’) indicated participants had 2 s to lift/view the phone and read aloud a series of digits. PRP was the number of digits read correctly. Each condition was repeated 5 times. 3D-motion analyses determined phone motion relative to the head, from which the variability in acceleration in viewing distance, and in the point of gaze in space in the up-down and right-left directions were assessed. A main effect of condition indicated PRP decreased with walking speed; particularly so for the Braced and Fixed conditions ( p = 0.022). Walking condition also affected the phone’s relative motion ( p < 0.001); post-hoc analysis indicated that acceleration variability for the Fast, Fixed and Braced conditions were increased compared to that for Slow and Customary speed walking ( p ≤ 0.05). There was an inverse association between phone acceleration variability and PRP ( p = 0.02). These findings may explain why walking speed slows when viewing a hand-held phone: at slower speeds, head motion is smoother/more regular, enabling the motion of the phone to be coupled with head motion, thus making fewer demands on the oculomotor system. Good coupling ensures that the retinal image is stable enough to allow legibility of the information presented on the screen.

Metabolic-based insecticide resistance mechanism and ecofriendly approaches for controlling of beet armyworm Spodoptera exigua: a review - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Xiaowei Li; Zhijun Zhang; Sakhawat Shah; Muhammad Imran; Mohammed A. Assiri; G. Mandela Fernández-Grandon; Nicolas Desneux; Muzammal Rehman; Shah Fahad; et al. (Environmental Science and Pollution Research, 2022)

Assessment of Non-Carcinogenic and Carcinogenic Risks Due to Ingestion of Vegetables Grown Under Sewage Water Irrigated Soils Near a 33 Years Old Landfill Site in Kolkata, India - Pabitra Kumar Mani; Agniva Mandal; Dipankar Mandal; Muhammad Irfan; G. C. Hazra; Sushanta Saha (Exposure and Health, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Effects of selenium on the uptake of toxic trace elements by crop plants: A review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Jörg Rinklebe; Daniel C. W. Tsang; Filip M. G. Tack; Ghulam Hasan Abbasi; Afzal Hussain; Avanthi Deshani Igalavithana; Byung Cheon Lee; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2021)

Environmental and human iodine and selenium status: lessons from Gilgit-Baltistan, North-East Pakistan - Saeed Ahmad; Elizabeth H. Bailey; Muhammad Arshad; Sher Ahmed; Michael J. Watts; Alex G. Stewart; Scott D. Young (Environmental Geochemistry and Health, 2021)
Iodine and selenium deficiencies are common worldwide. We assessed the iodine and selenium status of Gilgit-Baltistan, Pakistan. We determined the elemental composition (ICP-MS) of locally grown crops ( n = 281), drinking water ( n = 82), urine ( n = 451) and salt ( n = 76), correcting urinary analytes for hydration (creatinine, specific gravity). We estimated dietary iodine, selenium and salt intake. Median iodine and selenium concentrations were 11.5 (IQR 6.01, 23.2) and 8.81 (IQR 4.03, 27.6) µg/kg in crops and 0.24 (IQR 0.12, 0.72) and 0.27 (IQR 0.11, 0.46) µg/L in water, respectively. Median iodised salt iodine was 4.16 (IQR 2.99, 10.8) mg/kg. Population mean salt intake was 13.0 g/day. Population median urinary iodine (uncorrected 78 µg/L, specific gravity-corrected 83 µg/L) was below WHO guidelines; creatinine-corrected median was 114 µg/L but was unreliable. Daily selenium intake (from urinary selenium concentration) was below the EAR in the majority (46–90%) of individuals. Iodine and selenium concentrations in all crops were low, but no health-related environmental standards exist. Iodine concentration in iodised salt was below WHO-recommended minimum. Estimated population average salt intake was above WHO-recommended daily intake. Locally available food and drinking water together provide an estimated 49% and 72% of EAR for iodine (95 µg/day) and selenium (45 µg/day), respectively. Low environmental and dietary iodine and selenium place Gilgit-Baltistan residents at risk of iodine deficiency disorders despite using iodised salt. Specific gravity correction of urine analysis for hydration is more consistent than using creatinine. Health-relevant environmental standards for iodine and selenium are needed.

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

Understanding the Effects of Wind Intensity, Forward Speed, Pressure and Track on Generation and Propagation of Hurricane Irma Surges around Florida - Abram Musinguzi; Madinah Shamsu; Muhammad K. Akbar; Jason G. Fleming (Journal of Marine Science and Engineering, 2021)
In this study, it is demonstrated that hurricane wind intensity, forward speed, pressure, and track play an important role on the generation and propagation of coastal storm surges. Hurricane Irma, which heavily impacted the entire Florida peninsula in 2017, is used to study the storm surge sensitivity to varying storm characteristics. Results show that the west coast experiences a negative surge due to offshore wind of the approaching storm, but the positive surge returns after the hurricane eye passes over a location and wind became onshore. In the west coast peak, surges are intensified by an increase in onshore wind intensity and forward speed. In the Florida Keys, peak surges are intensified by an increase in wind intensity, a decrease in forward speed and a decrease in pressure. In southeast and east Florida, peak surges are intensified by decrease in pressure, although overall surges are less significant as the water can slide along the coastline. In the recessed coastline of Georgia-Carolinas, maximum surge is elevated by an increase in onshore wind intensity. Shifting the track westward increases peak surges on the west coast, while shifting the track eastward increases peak surge on the east coast. The results demonstrate a new understanding about the sensitivity of surge to varying parametric conditions and the importance of considering changes in the coastline orientation in storm surge predictions.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: The trade-off between economic growth and environmental quality: does economic freedom asymmetric matter for Pakistan? - Muhammad Tariq Majeed; Zhiyuan Yu; Adnan Maqbool; Mesfin G. Genie; Sana Ullah; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

Arbuscular mycorrhizal fungi and its major role in plant growth, zinc nutrition, phosphorous regulation and phytoremediation - Parashuram Bhantana; Muhammad Shoaib Rana; Xue-cheng Sun; Mohamed G. Moussa; Muhammad Hamzah Saleem; Muhamad Syaifudin; Ashrafuzzaman Shah; Amrit Poudel; Amar Bahadur Pun; Mufid Alam Bhat; Dhanik Lal Mandal; Sujit Shah; et al. (Symbiosis, 2021)

Mixed infections alter transmission potential in a fungal plant pathogen - Luke G. Barrett; Marcello Zala; Alexey Mikaberidze; Julien Alassimone; Muhammad Ahmad; Bruce A. McDonald; Andrea Sánchez‐Vallet (Environmental Microbiology, 2021)
Summary Infections by more than one strain of a pathogen predominate under natural conditions. Mixed infections can have significant, though often unpredictable, consequences for overall virulence, pathogen transmission and evolution. However, effects of mixed infection on disease development in plants often remain unclear and the critical factors that determine the outcome of mixed infections remain unknown. The fungus Zymoseptoria tritici forms genetically diverse infections in wheat fields. Here, for a range of pathogen traits, we experimentally decompose the infection process to determine how the outcomes and consequences of mixed infections are mechanistically realized. Different strains of Z . tritici grow in close proximity and compete in the wheat apoplast, resulting in reductions in growth of individual strains and in pathogen reproduction. We observed different outcomes of competition at different stages of the infection. Overall, more virulent strains had higher competitive ability during host colonization, and less virulent strains had higher transmission potential. We showed that within‐host competition can have a major effect on infection dynamics and pathogen population structure in a pathogen and host genotype‐specific manner. Consequently, mixed infections likely have a major effect on the development of septoria tritici blotch epidemics and the evolution of virulence in Z . tritici .

Synthesis, Structure Study, First-Principles Investigations and Luminescence Properties of Europium and Terbium Complexes - Bakhat Ali; Helio A. Stefani; Muhammad Imran; Ahmad Irfan; Mohammed A. Assiri; Maria Claudia F. C. Felinto; Muhammad Khalid; Abdullah G. Al-Sehemi (Journal of Fluorescence, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Mo-Inefficient Wheat Response Toward Molybdenum Supply in Terms of Soil Phosphorus Availability - Muhammad Shoaib Rana; Xuecheng Sun; Muhammad Imran; Zaid Khan; Mohamed G. Moussa; Muhammad Abbas; Parashuram Bhantana; Muhamad Syaifudin; Intisar Ud Din; Muhammad Younas; Md Ashrafuzzaman Shah; Javaria Afzal; et al. (Journal of Soil Science and Plant Nutrition, 2020)

Mitochondrial DNA diversity in the Khattak and Kheshgi of the Peshawar Valley, Pakistan - Muhammad Zubair; Brian E. Hemphill; Theodore G. Schurr; Muhammad Tariq; Muhammad Ilyas; Habib Ahmad (Genetica, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Muhammad Sohail Arshad; Sana Hassan; Amjad Hussain; Nasir Abbas; Israfil Kucuk; Kazem Nazari; Radeyah Ali; Suleman Ramzan; Ali Alqahtani; Eleftherios G. Andriotis; Dimitris G. Fatouros; Ming-Wei Chang; et al. (DARU Journal of Pharmaceutical Sciences, 2019)

First Results of a Bathymetric Survey of Palu Bay, Central Sulawesi, Indonesia following the Tsunamigenic Earthquake of 28 September 2018 - Marina C. G. Frederik; Udrekh; Ramadhan Adhitama; Nugroho D. Hananto; Asrafil; Shahab Sahabuddin; Muhammad Irfan; Omar Moefti; Dimas B. Putra; Bondan F. Riyalda (Pure and Applied Geophysics, 2019)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Understanding Hurricane Storm Surge Generation and Propagation Using a Forecasting Model, Forecast Advisories and Best Track in a Wind Model, and Observed Data—Case Study Hurricane Rita - Abram Musinguzi; Muhammad K. Akbar; Jason G. Fleming; Samuel K. Hargrove (Journal of Marine Science and Engineering, 2019)
Meteorological forcing is the primary driving force and primary source of errors for storm surge forecasting. The objective of this study was to learn how forecasted meteorological forcing influences storm surge generation and propagation during a hurricane so that storm surge models can be reliably used to forecast actual events. Hindcasts and forecasts of Hurricane Rita (2005) storm surge was used as a case study. Meteorological forcing or surface wind/pressure fields for Hurricane Rita were generated using both the Weather Research and Forecasting (WRF) full-scale forecasting model along with archived hurricane advisories ingested into a sophisticated parametric wind model, namely Generalized Asymmetric Holland Model (GAHM). These wind fields were used to forecast Rita storm surges. Observation based wind fields from the OceanWeather Inc. (OWI) Interactive Objective Kinematic Analysis (IOKA) model, and Best track wind data ingested into the GAHM model were used to generate wind fields for comparison purposes. These wind fields were all used to hindcast Rita storm surges with the ADvanced CIRCulation (ADCIRC) model coupled with the Simulating Waves Nearshore (SWAN) model in a tightly coupled storm surge-wave model referred to as ADCIRC+SWAN. The surge results were compared against a quality-controlled database of observed data to assess the performance of these wind fields on storm surge generation and propagation. The surge hindcast produced by the OWI wind field performed the best, although some high water mark (HWM) locations were overpredicted. Although somewhat underpredicted, the WRF wind fields forecasted wider surge extent and wetted most HWM locations. The hindcast using the Best track parameters in the GAHM and the forecast using forecast/advisories from the National Hurricane Center (NHC) in the GAHM produced strong and narrow wind fields causing localized high surges, which resulted in overprediction near landfall while many HWM locations away from wind bands remained dry.

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): Phase I: Segmentation - Philipp Berg; Samuel Voß; Sylvia Saalfeld; Gábor Janiga; Aslak W. Bergersen; Kristian Valen-Sendstad; Jan Bruening; Leonid Goubergrits; Andreas Spuler; Nicole M. Cancelliere; David A. Steinman; Vitor M. Pereira; et al. (Cardiovascular Engineering and Technology, 2018)

A novel homozygous mutation in SZT2 gene in Saudi family with developmental delay, macrocephaly and epilepsy - Muhammad Imran Naseer; Mohammad Khalid Alwasiyah; Angham Abdulrahman Abdulkareem; Rayan Abdullah Bajammal; Carlos Trujillo; Muhammad Abu-Elmagd; Mohammad Alam Jafri; Adeel G. Chaudhary; Mohammad H. Al-Qahtani (Genes & Genomics, 2018)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Understanding the interactions of diruthenium anticancer agents with amino acids - Alexey A. Nazarov; Maria-Grazia Mendoza-Ferri; Muhammad Hanif; Bernhard K. Keppler; Paul J. Dyson; Christian G. Hartinger (JBIC Journal of Biological Inorganic Chemistry, 2018)

An international program on Silk Road Disaster Risk Reduction–a Belt and Road initiative (2016–2020) - Lei Yu; Cui Peng; Amar Deep Regmi; Virginia Murray; Alessandro Pasuto; Giacomo Titti; Muhammad Shafique; Tilak Priyadarshana D. G (Journal of Mountain Science, 2018)

Resveratrol as an anti-cancer agent: A review - Abdur Rauf; Muhammad Imran; Masood Sadiq Butt; Muhammad Nadeem; Dennis G. Peters; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2018)

Identification, Characterization and Expression Profiles of Dof Transcription Factors in Pineapple (Ananas comosus L) - Syed Muhammad Azam; Yanhui Liu; Zia Ur Rahman; Hina Ali; Cheng Yan; Lulu Wang; S. V. G. N. Priyadarshani; Binyan Hu; Xinyu Huang; Junjie Xiong; Yuan Qin (Tropical Plant Biology, 2018)

Rapid Learning-Based and Geologically Consistent History Matching - Pejman Tahmasebi; Muhammad Sahimi; Mehrdad G. Shirangi (Transport in Porous Media, 2018)

Spatio-Temporal Patterns in the Coral Reef Communities of the Spermonde Archipelago, 2012–2014, II: Fish Assemblages Display Structured Variation Related to Benthic Condition - Jeremiah G. Plass-Johnson; Mirta Teichberg; Vanessa N. Bednarz; Astrid Gärdes; Jasmin P. Heiden; Muhammad Lukman; Sara Miñarro; Hauke Kegler; Laura Weiand; Christian Wild; Hauke Reuter; Sebastian C. A. Ferse (Frontiers in Marine Science, 2018)

Breaking Resilience for a Sustainable Future: Thoughts for the Anthropocene - Marion Glaser; Jeremiah G. Plass-Johnson; Sebastian C. A. Ferse; Muhammad Neil; Dewi Y. Satari; Mirta Teichberg; Hauke Reuter (Frontiers in Marine Science, 2018)

Spatio-Temporal Patterns in Coral Reef Communities of the Spermonde Archipelago, 2012–2014, I: Comprehensive Reef Monitoring of Water and Benthic Indicators Reflect Changes in Reef Health - Mirta Teichberg; Christian Wild; Vanessa N. Bednarz; Hauke F. Kegler; Muhammad Lukman; Astrid A. Gärdes; Jasmin P. Heiden; Laura Weiand; Nur Abu; Andriani Nasir; Sara Miñarro; Sebastian C. A. Ferse; et al. (Frontiers in Marine Science, 2018)

Antiplatelet activity, molecular docking and QSAR study of novel N′-arylmethylidene-3-methyl-1-phenyl-6-p-chlorophenyl-1H-pyrazolo[3,4-b] pyridine-4-carbohydrazides - Ayesha Ramzan; Sara Siddiqui; Ahmad Irfan; Abdullah G. Al-Sehemi; Aftab Ahmad; Francis Verpoort; Adeel H. Chughtai; Misbahul A. Khan; Munawar A. Munawar; Muhammad Asim Raza Basra (Medicinal Chemistry Research, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

A novel homozygous frameshift variant in the MCPH1 gene causes primary microcephaly in a consanguineous Saudi family - Muhammad Imran Naseer; Mahmood Rasool; Osama Yousef Muthaffar; Abdulrahman J. Sabbagh; Adeel G. Chaudhary; Mohammad H. Al-Qahtani (Genes & Genomics, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Allelopathic interference of alfalfa (Medicago sativa L.) genotypes to annual ryegrass (Lolium rigidum) - Hasan Muhammad Zubair; James E. Pratley; G. A. Sandral; A. Humphries (Journal of Plant Research, 2017)

Water Deficit Irrigation and Nitrogen Response of Sudan Grass under Arid Land Drip Irrigation Conditions - Samir G. Al‐Solaimani; Fahad Alghabari; Muhammad Zahid Ihsan; Shah Fahad (Irrigation and Drainage, 2017)
The present study evaluated the interactive effect of water deficit irrigation (WDI) and nitrogen application on Sorghum sudanense growth, biomass accumulation, nitrogen content and water productivity for two consecutive seasons and three cuts. The WDI of 50, 30 and 10% depletion ratios (different application rate and frequency) along with four levels (0, 100, 200 and 300 kg ha −1 ) of nitrogen fertilizer were applied in three splits. The WDI of 10% depletion ratio recorded significantly higher (15–17%) fresh and dry biomass accumulation of both leaf and stem as compared with WDI of 50%. Nitrogen application improved all growth traits irrespective of the applied levels of WDI, season and cut number. The interaction of WDI of 30% depletion ratio and N200 outcompeted all other treatments for plant nitrogen and protein contents, as the resulting increment was 10–22% higher as compared to control. Of the different cut numbers, the first cutting ascribed the maximum value for plant protein contents and stated up to 32% improvement over second and third cuttings. By increasing the rate of nitrogen application, a significant increment in crop water productivity was also measured that attributed at least a threefold higher value for stem over leaf. In essence, WDI of 10% depletion ratio and nitrogen rate of 200 kg ha −1 were the optimum levels that improved Sudan grass growth, biomass and water use efficiency; moreover, the 30% depletion ratio favoured plant nitrogen content. By using a WDI approach, we can improve our forage yield with a limited amount of water by increasing irrigation frequency. Copyright © 2017 John Wiley & Sons, Ltd.

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Experimental analysis of the effects of consumer exclusion on recruitment and succession of a coral reef system along a water quality gradient in the Spermonde Archipelago, Indonesia - Jeremiah G. Plass-Johnson; Jasmin P. Heiden; Nur Abu; Muhammad Lukman; Mirta Teichberg (Coral Reefs, 2016)

Co-occurrence of arsenic and fluoride in the groundwater of Punjab, Pakistan: source discrimination and health risk assessment - Atta Rasool; Tangfu Xiao; Zenab Tariq Baig; Sajid Masood; Khan M. G. Mostofa; Muhammad Iqbal (Environmental Science and Pollution Research, 2015)

Correlation of Arsenic Levels in Smokeless Tobacco Products and Biological Samples of Oral Cancer Patients and Control Consumers - Sadaf S. Arain; Tasneem G. Kazi; Hassan I. Afridi; Farah N. Talpur; Atif G. Kazi; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Muhammad A. Kamboh (Biological Trace Element Research, 2015)

Genetic analysis suggests a shared origin of Punica granatum cultivars in Oman with cultivars from the center of origin, Iran - Abdullah M. Al-Sadi; Ahmed R. AL-Fahdi; Rashid A. Al-Yahyai; Aisha G. Al-Ghaithi; Fahad A. Al-Said; Muhammad J. Soleiman (Genetic Resources and Crop Evolution, 2015)

Estimation of lead in biological samples of oral cancer patients chewing smokeless tobacco products by ionic liquid-based microextraction in a single syringe system - Sadaf S. Arain; Tasneem G. Kazi; Asma J. Arain; Hassan I. Afridi; Muhammad B. Arain; Kapil D. Brahman; Naeemullah; Abdul H. Panhwar; Mariam S. Arain (Environmental Science and Pollution Research, 2015)

Dissemination via the lymphatic or angiogenic route impacts the pathology, microenvironment and hypoxia-related drug response of lung metastases - Roben G. Gieling; Richard J. Fitzmaurice; Brian A. Telfer; Muhammad Babur; Kaye J. Williams (Clinical & Experimental Metastasis, 2015)

Application of Short-Offset TEM (SOTEM) Technique in Mapping Water-Enriched Zones of Coal Stratum, an Example from East China - Wei-ying Chen; G. Q. Xue; Younis Khan Muhammad; L. J. Gelius; Nan-nan Zhou; Hai Li; Hua-sen Zhong (Pure and Applied Geophysics, 2015)

Knowledge, attitude, and practice of Indonesian farmers regarding the use of personal protective equipment against pesticide exposure - Maria G. C. Yuantari; Cornelis A. M. Van Gestel; Nico M. Van Straalen; Budi Widianarko; Henna R. Sunoko; Muhammad N. Shobib (Environmental Monitoring and Assessment, 2015)

Changes in the variability and periodicity of precipitation in Scotland - Muhammad Afzal; Alexandre S. Gagnon; Martin G. Mansell (Theoretical and Applied Climatology, 2015)

Evaluation of PAH contamination in soil treated with solid by-products from shale pyrolysis - Jaqueline Nicolini; Muhammad Y. Khan; M. Matsui; Lílian C. Côcco; Carlos I. Yamamoto; Wilson A. Lopes; Jailson B. de Andrade; Clenio N. Pillon; Gregorio G. Carbajal Arizaga; Antonio S. Mangrich (Environmental Monitoring and Assessment, 2015)

Co-exposure of arsenic and cadmium through drinking water and tobacco smoking: Risk assessment on kidney dysfunction - Muhammad B. Arain; Tasneem G. Kazi; Jameel Ahmed Baig; Hassan I. Afridi; Sarajuddin; Kapil D. Brehman; Haleem Panhwar; Sadaf S. Arain (Environmental Science and Pollution Research, 2015)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Tephrochronology of the Toba tuffs: four primary glass populations define the 75‐ka Youngest Toba Tuff, northern Sumatra, Indonesia - J. A. WESTGATE; N. J. G. PEARCE; W. T. PERKINS; S. J. PREECE; C. A. CHESNER; R. F. MUHAMMAD (Journal of Quaternary Science, 2013)
Four primary glass populations, well defined by their Sr, Ba and Y concentrations, occur in the Youngest Toba Tuff (YTT), which was deposited during a supereruption of the Toba caldera complex in northern Sumatra 75 ka. Average concentrations of major and trace elements indicate a coherent, systematic variation of glass composition across populations. No clear pattern in the areal distribution of these four glass groups can be discerned. The multiple glass populations of the YTT easily distinguish it from the single homogeneous glass population of the Middle Toba Tuff (∼500 ka), as represented by its basal vitrophyre, and that of the Oldest Toba Tuff (∼800 ka), as represented by ash Layer D at the Ocean Drilling Program site 758 in the Indian Ocean.

Synthesis, crystal structure and β-glucuronidase inhibition activity of some new hydrazinecarboxamides and their 1,2,4-triazole derivatives - Muhammad Hanif; Imtiaz Khan; Nasim Hasan Rama; Shagufta Noreen; Muhammad Iqbal Choudhary; Peter G. Jones; Mazhar Iqbal (Medicinal Chemistry Research, 2012)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Determination of radioactive elements and heavy metals in sediments and soil from domestic water sources in northern peninsular Malaysia - Bashir G. Muhammad; Mohammad Suhaimi Jaafar; Azhar Abdul Rahman; Farouk Abdulrasheed Ingawa (Environmental Monitoring and Assessment, 2012)

Local calibration of remotely sensed rainfall from the TRMM satellite for different periods and spatial scales in the Indus Basin - Muhammad Jehanzeb Masud Cheema; Wim G. M. Bastiaanssen (International Journal of Remote Sensing, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Comparison of biological parameters between the invasive B biotype and a new defined Cv biotype of Bemisia tabaci (Hemiptera: Aleyradidae) in China - Bao-Li Qiu; Fang Dang; Shao-Jian Li; Muhammad Z. Ahmed; Feng-Liang Jin; Shun-Xiang Ren; Andrew G. S. Cuthbertson (Journal of Pest Science, 2011)

Analysis of Cross Correlations Between Well Logs of Hydrocarbon Reservoirs - Hassan Dashtian; G. Reza Jafari; Zahra Koohi Lai; Mohsen Masihi; Muhammad Sahimi (Transport in Porous Media, 2011)

Determination of Arsenic in Scalp Hair of Children and its Correlation with Drinking Water in Exposed Areas of Sindh Pakistan - Tasneem G. Kazi; Jameel A. Baig; Abdul Q. Shah; Muhammad Balal Arain; Muhammad Khan Jamali; Ghulam A. Kandhro; Hassan I. Afridi; Nida F. Kolachi; Sumaira Khan; Sham K. Wadhwa; Faheem Shah (Biological Trace Element Research, 2011)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Silicatein-mediated incorporation of titanium into spicules from the demosponge Suberites domuncula - Filipe Natalio; Enrico Mugnaioli; Matthias Wiens; Xiaohong Wang; Heinz C. Schröder; Muhammad Nawaz Tahir; Wolfgang Tremel; Ute Kolb; Werner E. G. Müller (Cell and Tissue Research, 2010)

In Vitro Distribution of Gold in Serum Proteins after Incubation of Sodium Aurothiomalate and Auranofin with Human Blood and its Pharmacological Significance - Mohammad S. Iqbal; Syed G. Taqi; Muhammad Arif; Muhammad Wasim; Muhammad Sher (Biological Trace Element Research, 2009)

Enhancing the performance of transplanted coarse rice by seed priming - Muhammad Farooq; Shahzad M. A. Basra; N. Ahmad; G. Murtaza (Paddy and Water Environment, 2009)

Enzymatic production of biosilica glass using enzymes from sponges: basic aspects and application in nanobiotechnology (material sciences and medicine) - Heinz C. Schröder; David Brandt; Ute Schloßmacher; Xiaohong Wang; Muhammad Nawaz Tahir; Wolfgang Tremel; Sergey I. Belikov; Werner E. G. Müller (The Science of Nature, 2007)

Quantitative trait loci for early maturity and their potential in breeding for earliness in Brassica juncea - Tariq Mahmood; Muhammad H. Rahman; Gary R. Stringam; Francis Yeh; Allen G. Good (Euphytica, 2007)

Impact of growing maize (Zea mays) on the decomposition of incorporated fresh alfalfa residues - S. Muhammad; T. Müller; J. Mayer; R. G. Joergensen (Biology and Fertility of Soils, 2007)

Decomposition of pea and maize straw in Pakistani soils along a gradient in salinity - S. Muhammad; T. Müller; R. G. Joergensen (Biology and Fertility of Soils, 2006)

Defective glycosylation of decorin and biglycan, altered collagen structure, and abnormal phenotype of the skin fibroblasts of an Ehlers–Danlos syndrome patient carrying the novel Arg270Cys substitution in galactosyltransferase I (β4GalT-7) - Daniela G. Seidler; Muhammad Faiyaz-Ul-Haque; Uwe Hansen; George W. Yip; Syed H. E. Zaidi; Ahmad S. Teebi; Ludwig Kiesel; Martin Götte (Journal of Molecular Medicine, 2006)

Persistent Organic Pollutants in Little Egret Eggs from Selected Wetlands in Pakistan - C. Sanpera; X. Ruiz; L. Jover; G. Llorente; R. Jabeen; A. Muhammad; E. Boncompagni; M. Fasola (Archives of Environmental Contamination and Toxicology, 2003)

A Preliminary Comparison of Plasma Fibrinogen Concentrations, Leukocyte Numbers and Erythrocyte Sedimentation Rate as Non-Specific Indicators of Inflammatory Conditions in Buffalo (Bubalis Bubalis) - M. Zargham Khan; G. Muhammad; A. Umar; S. Ali Khan (Veterinary Research Communications, 1997)

Sex hormone-binding globulin, serum testosterone, and androgen receptors in the skin in papulopustular and conglobata forms of acne vulgaris - N. E. Kushlinskii; I. V. Salamova; S. A. Masyukova; A. Kh. Muhammad; V. G. Degtyar’; V. A. Samsonov (Bulletin of Experimental Biology and Medicine, 1997)